2021
DOI: 10.1371/journal.pcbi.1008919
|View full text |Cite
|
Sign up to set email alerts
|

Detecting adherence to the recommended childhood vaccination schedule from user-generated content in a US parenting forum

Abstract: Vaccine hesitancy is considered as one of the leading causes for the resurgence of vaccine preventable diseases. A non-negligible minority of parents does not fully adhere to the recommended vaccination schedule, leading their children to be partially immunized and at higher risk of contracting vaccine preventable diseases. Here, we leverage more than one million comments of 201,986 users posted from March 2008 to April 2019 on the public online forum BabyCenter US to learn more about such parents. For 32% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Compared to North America and North European countries, confidence in the safety of vaccination is especially low in Western and Eastern Europe, with 59% and 40% respectively agreeing that vaccines are safe (Wellcome Trust 2018). It has also been found that parents who deviate from recommended childhood vaccination schedules are more likely to focus on potential serious adverse reactions to vaccination (Betti et al 2021) and display lower trust in science (Wellcome Trust 2018). Vaccine hesitancy is not only related to reluctance to engage with scientific evidence (Browne et al 2015), but it has also been linked to the emphasis on religious identity (Kata 2010), alternative or holistic health methods (Kalimeri et al 2019;Betti et al 2021), and certain political attitudes (Yaqub et al 2014;Browne et al 2015).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to North America and North European countries, confidence in the safety of vaccination is especially low in Western and Eastern Europe, with 59% and 40% respectively agreeing that vaccines are safe (Wellcome Trust 2018). It has also been found that parents who deviate from recommended childhood vaccination schedules are more likely to focus on potential serious adverse reactions to vaccination (Betti et al 2021) and display lower trust in science (Wellcome Trust 2018). Vaccine hesitancy is not only related to reluctance to engage with scientific evidence (Browne et al 2015), but it has also been linked to the emphasis on religious identity (Kata 2010), alternative or holistic health methods (Kalimeri et al 2019;Betti et al 2021), and certain political attitudes (Yaqub et al 2014;Browne et al 2015).…”
Section: Related Workmentioning
confidence: 99%
“…It has also been found that parents who deviate from recommended childhood vaccination schedules are more likely to focus on potential serious adverse reactions to vaccination (Betti et al 2021) and display lower trust in science (Wellcome Trust 2018). Vaccine hesitancy is not only related to reluctance to engage with scientific evidence (Browne et al 2015), but it has also been linked to the emphasis on religious identity (Kata 2010), alternative or holistic health methods (Kalimeri et al 2019;Betti et al 2021), and certain political attitudes (Yaqub et al 2014;Browne et al 2015). However, public health communication campaigns may be producing an effect.…”
Section: Related Workmentioning
confidence: 99%
“…Lack of medicines information in children, un-licensed medicines use and di culties to develop paediatric medicines [45,48] prevents the effective and safe use of medicines. SM articles are focused in either a speci c therapeutic area or DRP such as non-compliance with vaccines schedules, found in (60%) of the posts [37] and the di culties to administer oral formulations to young children and strategies parents use to do it [20]. Most affected ages were infants (165, 26%) and children (98,15%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Web-RADR project shared recommendations such as to focus on niche populations and as a source to complement traditional like forums [6], to decrease irrelevant data. Paediatric focused searches for product or disease-speci c have been studied in Facebook [22][23][24][25], Pinterest [26], Twitter [27][28][29][30][31] and forums [12,20,[32][33][34][35][36][37][38]. Most authors searched for ADR mentions in SM for particular medicines [39,40] and ADR [41] but, to date, none conducted a global analysis in paediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…Words in the LibertyMFD were selected after extensive experimentation on two different data-driven lexicon generation approaches. Further, we assessed the performance of the lexicon on a manually annotated dataset of usergenerated text regarding the issue of vaccine hesitancy, one of the topics where liberty is known to be a critical factor [7].…”
Section: Discussionmentioning
confidence: 99%